Producto turístico y facilidades turísticas en el Complejo Arqueológico Baños Cañari Inca, comunidad Coyoctor, cantón El Tambo, provincia del Cañar - Duchi Tenemaza, Rosa Elizabeth (2023)
The research project objective is to analyze the relationship between tourist products and tourist facilities in the Archaeological Complex Baños Cañari Inca, a community of Coyoctor, canton of Tambo, province of Cañar. A correlational, cross-sectional, non-experimental design research was carried out for information collection in two stages. The first is the application of surveys to 40 providers of tourist services such as lodging, food and beverages, tourist transport, and travel agencies, and the second to 40 inhabitants of the community of Coyoctor. Cronbach's Alpha method was used to determine the reliability of the research instruments, and to test the hypotheses that led to the conclusions and recommendations, Spearman's Rho method was used. The process and analysis of the data were carried out using the SPSS statistical program, version 26. The information gathered established that there is no relationship between tourism products and facilities in the Baños Cañari Inca Archaeological Complex. Finally, after analyzing the results, conclusions, and recommendations, a proposal is presented that responds to the inadequate tourist facilities in the Baños Cañari Inca Archaeological Complex, for which a SWOT analysis was carried out, where the implementation of strategies that aim to improve tourist facilities such as tourist signage, which helps the tourist development of the place, is suggested.